Revitalizing Public Spaces Through the Sukoharjo Creative and Culinary Market as a Collaborative Platform for Communities, MSMEs, and Students to Increase Creativity and Economic Independence of Local Communities - Putri, Aninda Dyah Hayu Pinasti; Salim, Salim (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This community service program was conducted to address the lack of promotion space and development opportunities for the creative economy sector in Sukoharjo Regency. The program’s partners included the Department of Trade, Cooperatives, and Small and Medium Enterprises (Disdagkop and SMEs), local micro, small, and medium enterprises (MSMEs), creative communities, and vocational high school students. The main objective was to revitalize public space through the Sukoharjo Creative and Culinary Market (SUKREMA), a curated creative bazaar designed to foster cross-sector collaboration. The implementation applied a participatory approach and project-based learning method through several stages: socialization, product branding and design training, creative work curation, and bazaar implementation at the Regional Potential Promotion Center (GPPPD) in Sukoharjo. The results showed improvements in participants’ abilities in product innovation, packaging design, and digital marketing strategies. Moreover, a digital catalog and reusable modular booth design were produced to support future events. This program successfully transformed public spaces into inclusive and sustainable creative economy hubs.